The thermogenic effect of mirabegron ingestion during cool conditions - Gorini Pereira, Felipe; Ryan, Caleb T.; Miller, Spencer; Watters, Andrew; Mickleborough, Timothy D.; Schlader, Zachary J.; Bell, Christopher; Johnson, Blair D. (Frontiers in Physiology, 2025)
IntroductionBrown adipose tissue (BAT) is highly thermogenic and can be stimulated by cold exposure or mirabegron, a β3-adrenergic receptor agonist. However, it is currently not known whether the thermogenic effects of mirabegron are observed during exposure to cool temperatures. We tested the hypotheses that energy expenditure and BAT activation would be greater following mirabegron ingestion versus a placebo (PLA).MethodsEleven healthy adults (5 women) completed four, double-blind, randomized visits to the laboratory involving the acute ingestion of 100, 150, and 200 mg of mirabegron or PLA. Following ingestion, subjects rested for 6 h in a whole-body indirect room calorimeter (20 °C, 50% RH). Cumulative energy expenditure was calculated for each study visit. Using infrared thermography, supraclavicular BAT activity was assessed via the area under the curve (AUC) for supraclavicular skin temperature (Tsc) expressed relative to sternal skin temperature for each visit.ResultsCumulative energy expenditure was greater following ingestion of 100 mg (494 ± 75 kcal; p < 0.001), 150 mg (481 ± 67 kcal; p = 0.017), and 200 mg (492 ± 69 kcal; p = 0.001) of mirabegron vs. PLA (456 ± 67 kcal), with no differences between doses (p > 0.05). The AUC for Tsc was greater following ingestion of 100 mg (12.54 ± 7.51 °C × min; p = 0.011) and 150 mg (10.01 ± 6.05 °C × min; p = 0.021) doses of mirabegron vs. PLA (4.74 ± 3.86 ° × min), but not the 200 mg dose (9.17 ± 5.95 ° × min; p = 0.067).DiscussionOur data indicate β3-adrenergic receptor activation of supraclavicular BAT via mirabegron ingestion enhances thermogenesis in cool environments.